Deep learning based arrhythmia classification on low-cost and low-compute MCU - Zishan, Md Abu Obaida; Shihab, H M; Rahman, Gazi Mashrur; Islam, Sabik Sadman; Riya, Maliha Alam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.